Effects of different soil ameliorants on karee trees (searsia Lancea) growing on mine tailings dump soil - part I: pot trials - Lange, Christian A.; Kotte, Karsten (International journal of phytoremediation, 2012)
Rehabilitation of mine tailings dams is often a challenge due to a lack of nutrients and a poor humus reservoir prevailing in tailings soils. This is especially true for establishing longer lived species such as trees. For these reasons the effects of different soil ameliorants (woodchips compost, vermicompost, mature sewage sludge), added to the root system of Karee (Searcia lancea) saplings were tested in pot trials. Those pots were filled with platinum and gold tailings substrate as well as red clay soil, respectively. For three months plants remained in a greenhouse and were subsequently moved to a test field outside. Throughout the test period regular chl a fluorescence measurements were taken and subjected to JIP-test quantifying changes in photosynthetic vitality status. Additionally, growth measurements and one-off leaf analysis were carried out. Test plants growing on mine tailings experienced an up to 35% higher average photosynthetic vitality (PIABS) and improved nutrient supply, when treated with mature sewage sludge. Consequently, sewage sludge treated plants showed a higher biomass build-up rate and an up to 55% higher diameter growth, compared to control. In summary the experiments present a low cost alternative for reforestation enterprises on platinum and gold tailings dams in South Africa.
Published online:07 Jun 2012
Gesehen am 15.10.2018